(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2018)
Despite being a common occurrence in the Later Middle ages, domestic violence hasn’t left many traces in the archives, especially when the victims were women of low social profile. It is, therefore, interesting the presence, within the Milanese Diplomatic Correspondence, of a corpus of letters dealing with an episode of violence which took place in Parma in the spring of 1461 and involved a young girl, agnese de Crovaria, a servant in the household of the Counts Manfredi, who was first raped and then savagely beaten. thanks to these sources, it has been possible to reconstruct the dynamics of a violence which happened in the secrecy of the domestic walls. attention has been also paid to the context in which the violence took place, and to the behavior of Milanese authorities, that acted carefully in handling the case. What stands out is the central role played by women, both as victims and as active participants in the violence: the episode of femaleon- female violence that followed the assault committed by antonio Manfredi reveals, in the women involved, i.e. his wife and his mother-in-law, an unexpected potential for violence. DOI 10.17464/9788867742745